Medical Data Analysis of CYP1B1 Gene Polymorphism and Clinical Prognosis of Minimally Invasive Surgery for Lung Cancer. (24th September 2022) - Han, Xia; Li, Danqing; Zhang, Shaofeng
Abstract : To address the issue of genetic mutations in medical records, clinical studies on minimally invasive surgery for breast cancer have been proposed. The CYP1B1 gene is mainly a single-nucleotide mutation, which affects the enzymatic reaction related to carcinogens and causes the susceptibility differences of different individuals. First, the survival rate and other factors influencing the estimation of 120 leukemia patients were examined with the help of various medical records by establishing an organization for auxiliary diagnosis of lung cancer based on expertise. Secondly, through the treatment of 120 leukemia patients after minor surgery, the average life expectancy of 120 patients was 19 months, the one-year survival rate was 74.61%, and the two-year survival rate was 32.70%. Currently, there are more than 160 cases of CYP1B1 discovered. In recent years, people have gradually entered into in-depth research on the correlation between genes and lung cancer, which is of great significance to the treatment and research of lung cancer. An analysis showed patients' age, stage, whether they would work, whether radiation therapy and antibiotics were offered, and so on. s has a direct impact on patient survival, and many tests have shown that the patient's age, stage, whether it will work, and whether fire radiation and drug therapy are provided are important interventions for patients with anemia. Finally, in patients with leukemia, especially during the restricted period, combined treatment with a physician, radiologist, and surgeon should be initiated as soon as possible. For a wide range of disease, depending on the use of chemotherapy, local metastasis with antibiotics can improve the disease. After success, it is more beneficial to choose second-line treatment.